Severe Hypoglycemia Contributing to Cognitive Dysfunction in Diabetic Mice Is Associated With Pericyte and Blood–Brain Barrier Dysfunction - Lin, Lu; Wu, Yubin; Chen, Zhou; Huang, Lishan; Wang, Lijing; Liu, Libin (Frontiers in Aging Neuroscience, 2021)
Background: Severe hypoglycemia can cause cognitive impairment in diabetic patients, but the underlying molecular mechanism remains unclear. Objective: To assess the effect of severe hypoglycemia on cognitive function in diabetic mice to clarify the relationship between the mechanism and dysfunction of pericytes and the blood–brain barrier (BBB). Method: We established type 1 diabetes mellitus in 80 male C57BL/6J mice by intraperitoneal injection of streptozotocin (150 mg/kg). Further intraperitoneal injection of short-acting insulin induced severe hypoglycemia. The mice were divided into normal, diabetes, and diabetic + severe hypoglycemia groups, and their blood glucose and general weight index were examined. Pericyte and BBB morphology and function were detected by histological and western blot analyses, BBB permeability was detected by Evans blue staining, and cognitive function was detected with the Morris water maze. Results: Severe hypoglycemia aggravated the histological damage, BBB damage, brain edema, and pericyte loss in the diabetic mice. It also reduced the expression of the BBB tight junction proteins occludin and claudin-5, the expression of the pericyte-specific markers PDGFR-β (platelet-derived growth factor receptor-β) and α-SMA, and increased the expression of the inflammatory factor MMP9. At the same time, diabetic mice with severe hypoglycemia had significantly reduced cognitive function. Conclusion: Severe hypoglycemia leads to cognitive dysfunction in diabetic mice, and its possible mechanism is related to pericyte dysfunction and BBB destruction.